Sonodynamic therapy for the treatment of atherosclerosis - Yan Zhang; Ying Yang; Yudi Feng; Xueyan Gao; Liping Pei; Xiaopan Li; Bingxin Gao; Lin Liu; Chengzeng Wang; Shuochen Gao (Elsevier, 2024)
Atherosclerosis (AS) is a chronic inflammatory disease of large and medium-sized arteries that leads to ischemic heart disease, stroke, and peripheral vascular disease. Despite the current treatments, mortality and disability still remain high. Sonodynamic therapy (SDT), a non-invasive and localized methodology, has been developed as a promising new treatment for inhibiting atherosclerotic progression and stabilizing plaques. Promising progress has been made through cell and animal assays, as well as clinical trials. For example, the effect of SDT on apoptosis and autophagy of cells in AS, especially macrophages, and the concept of non-lethal SDT has also been proposed. In this review, we summarize the ultrasonic parameters and known sonosensitizers utilized in SDT for AS; we elaborate on SDT's therapeutic effects and mechanisms in terms of macrophages, T lymphocytes, neovascularization, smooth muscle cells, lipid, extracellular matrix and efferocytosis within plaques; additionally, we discuss the safety of SDT. A comprehensive summary of the confirmed effects of SDT on AS is conducted to establish a framework for future researchers.